Building ethical guidelines to produce official statistics: the statistical ethics system (SETE) for the national administrative department of statistics (DANE) in Colombia - Hernández-Zambrano, David (Journal of global ethics, 2023)
This article describes and analyzes the design and functioning of the Statistical Ethics System (SETE) in Colombia’s National Statistical Office. It presents the methodology and general process of planning and implementation of the System, supported by a conceptual analysis of the requirements for an ethical functioning of official statistics. The general objective of the article is to make a practical contribution to the understanding of conceptual and practical features that ought to be considered in the implementation of an ethical system in the operation of the public sector, particularly in the area of the production of official statistics. The text is divided into five parts. In the first part, we make a general introduction to the ethical value of official statistics. In the second and third parts, we make a presentation and analysis of the principles and risks that were selected as the basic ethical framework for the production of official statistics at the National Administrative Department of Statistics (DANE). The fourth section presents the conceptual and practical bases of how SETE operates. The fifth section we present some concluding remarks.